AUTOMATIC POLYALUMINIUM CHLORIDE (PAC) DOSING CONTROL SYSTEM FOR WATER PURIFICATION USING NODEMCU-ESP32 - Fauzan Amri; Bagus Dharmawan Hadi; Tri Haryanti; Revan Lutfiar Rizky; Sri Rahayu; Aulia Wanda Alifah (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
This study discusses the design and implementation of a control system for a water pump used to inject PAC solution into raw water, thereby producing treated water that meets quality standards. The pump’s operating duration is adaptively controlled based on the turbidity level of the water to be clarified. The system employs a turbidity sensor as the input signal, which generates data to be processed by a NodeMCU-ESP32 device serving as the central controller. Subsequently, the controller issues commands to the water pump, functioning as the actuator, to perform the PAC injection process. Experiments were conducted on three types of water sources, namely river water, paddy field water, and groundwater, with initial turbidity levels of 29, 35, and 64 NTU, respectively. The results showed that all water samples were successfully clarified to a turbidity value of 0 NTU within 47, 120, and 137 minutes, respectively. At the beginning of the treatment process, turbidity value readings exhibited fluctuations due to the initial mixing of PAC solution with raw water. However, the turbidity values steadily decreased once the PAC and suspended particles were fully settled. To facilitate monitoring, the system is equipped with an IoT feature via the Firebase platform, which displays numerical indicators including water volume, turbidity level, pump speed, pump operating duration, and water status classified according to clarity. This innovation is expected to contribute as an effective water purification automation technology, expecially for small- and medium-scale industries.